A subset of Vγ9Vδ2 T cells help B cells for antibody production (Hematology Meeting Reports, 2009)
Vγ9Vδ2 T lymphocytes recognize nonpeptidic antigens and mount effector functions in cellular immune responses against microorganisms and tumors, but little is known about their role in antibody-mediated immune responses. Here we report on the identification of a unique subset of Vγ9Vδ2 T cells which express the costimulatory molecules ICOS and CD40L, secrete IL-2, IL-4 and IL-10 and help B cells for antibody production. These properties portray CXCR5+ Vγ9Vδ2 T cells as a distinct memory T cell subset with B cell helper function.